Pengaruh Kualitas Produk, Citra Merek dan Harga Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Produk Pleu Baby - Afifah Damayanti, Netta; Sugiyanto, Sugiyanto (Jurnal Etnik: Ekonomi-Teknik, 2023)
This phenomenon, business people must strive to provide quality products, a good brand image and competitive prices to improve people's lives. The demand for goods should increase among consumers who are in a position of greater variety and variety because their products offer a wide range of choices and services. The purpose of this study was to determine the effect of product quality, brand image, price and consumer satisfaction on customer loyalty Pleu baby Tangerang baby clothes. Sampling was carried out using a non-probability sampling method with a purposive sampling technique by identifying 150 respondents with a minimum age of 20 years and purchasing baby clothes at Pleu Baby at least once. Data analysis techniques used in this study consisted of validity test, reliability test, classical assumption test, descriptive analysis and path analysis. The results showed that product quality has a significant effect on customer satisfaction, product image has a significant effect on customer satisfaction, price has a significant effect on customer satisfaction, customer satisfaction has a significant effect on customer loyalty, and product quality has a significant effect on customer loyalty, product image has a large effect on loyalty customers, price has a big effect on customer loyalty. Customer satisfaction as an intervening variable has a greater influence between product quality, brand image and price on customer retention of Pleu Baby Tangerang baby clothes.